Defect-regulated ultrathin molybdenum disulfide loaded organic manganese complex heterostructure catalyst as well as preparation method and application thereof
By preparing defect-regulated ultra-thin molybdenum disulfide-supported heterostructure catalysts for organic manganese complexes, the problem of poor catalytic efficiency and stability in photocatalytic CO2 and H2O reactions is solved, and the methanol generation with high selectivity and high yield is achieved. Industrial application.
Patent Information
- Application Number
- CN202411643636.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-18
AI Technical Summary
In the catalytic reaction of CO2 and H2O, existing photocatalysts have problems such as insufficient catalytic efficiency, poor stability and high-speed carrier recombination, which limits the selectivity and yield of methanol.
Using defect-regulated ultra-thin molybdenum disulfide-supported heterostructure catalysts of organic manganese complexes, a layered organic manganese complex is formed by mixing manganese salt, bipyridine and oxalic acid with ultra-thin molybdenum sulfide, and then peel and roasting by ultrasonic peeling and calcining. Steps: Prepare defect-rich catalysts to improve the adsorption activation and photocatalytic reaction efficiency of CO2.
High selectivity and high stability photocatalytic CO2 reduction is achieved, which significantly improves the selectivity and yield of methanol, and does not require reaction aids under low temperature and low pressure conditions, which significantly improves catalytic activity.
Smart Images

Figure CN119259120A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic materials, and in particular to a defect-controlled ultra-thin molybdenum disulfide-loaded organic manganese complex heterostructure catalyst, and a preparation method and application thereof. Background Art
[0002] Excessive use of fossil fuels has led to a continuous increase in carbon dioxide emissions, which has had many negative impacts on the global environment and greatly hindered the sustainable development of human society. The light-driven conversion of CO2 into valuable green and clean fuels (methanol, ethanol) not only helps to reduce greenhouse gas emissions, but also can create a carbon-neutral energy utilization model, which is of great significance for achieving sustainable development. However, efficient photocatalysts require fast charge transfer and low electron-hole recombination rates to promote redox reactions, which is a key bottleneck hindering the widespread application of CO2 photoreduction to methanol.
[0003] Two-dimensional ultrathin photocatalysts are rich in defects, have suitable band gap potentials and tunable optical properties, and have been proven to be a material that accelerates vertical charge separation and planar proton transfer. However, due to surface stress, defect-rich ultrathin catalysts often have structural instability. During the catalytic process, strong interactions can lead to their aggregation and dissociation, affecting CO2 catalytic activity and stability. In addition, the problem of easy and rapid recombination of electrons and holes also limits the improvement of the photoactivity efficiency of single two-dimensional materials.
[0004] In recent years, people have conducted extensive research on defect-rich two-dimensional heterojunction photocatalysts. CN118287111A discloses a method for preparing a bismuth / molybdenum / zinc vacancy-rich bismuth molybdate / zinc selenide heterojunction photocatalyst, wherein a molybdenum source, a surfactant and a bismuth source are hydrothermally synthesized to produce defect-rich bismuth molybdate, which is then ground and ion-dialyzed with hydrothermally synthesized zinc selenide to produce bismuth / molybdenum / zinc vacancy-rich bismuth molybdate / zinc selenide. This photocatalytic material has high purity, stable strength, low surface charge transfer resistance, high photocurrent density and excellent catalytic performance.
[0005] CN118237053A discloses a method for preparing a three-phase Z-type heterojunction photocatalyst of molybdenum selenide / oxygen-deficient bismuth oxybromide@gold, wherein oxygen-deficient BiOBr nanospheres are prepared by a solvothermal method, and then monodisperse Au nanoparticles are prepared by directly reacting tetrachloroauric acid with oleylamine in toluene, and the monodisperse Au nanoparticles are compounded with oxygen-deficient BiOBr to prepare BiOBr@Au nanosphere core-shell structure; finally, MoSe2 / oxygen-deficient BiOBr@Au three-phase composite material is prepared by hydrothermal reaction. It solves the problems of low photogenerated electron-hole separation rate, narrow full-spectrum response range and poor stability in existing bismuth-based photocatalysts. However, the synthesis methods used in these heterostructure catalysts are relatively complicated, involving a large number of synthetic materials, including highly toxic organic substances, which are contrary to the concept of green synthesis of materials; and their reaction activity has not reached an ideal level.
[0006] The applicant's early research CN 116273180 A disclosed the discovery of a catalyst with a heterogeneous structure of an organic zinc complex and molybdenum sulfide, a preparation method and an application, the preparation comprising the following steps: step 1, preparing flaky molybdenum sulfide; step 2, preparing a layered organic zinc complex; step 3, dispersing the molybdenum sulfide and the organic zinc complex in a solvent respectively, adding a solution containing the organic zinc complex to a solution containing molybdenum sulfide for reaction, and obtaining the catalyst by centrifugation, washing, drying and calcination, and the catalyst photocatalyzed CO2 to obtain a methanol selectivity of nearly 90%. However, creating a more efficient catalyst is still the research direction of the researchers. Summary of the invention
[0007] Aiming at the problems of insufficient catalytic efficiency and poor stability in the efficient preparation of methanol by photocatalytic reaction of CO2 and H2O, as well as the problem of high-speed carrier recombination caused by the unstable structure of the catalyst itself, the present invention provides a defect-controlled ultra-thin molybdenum disulfide-loaded organic manganese complex heterostructure catalyst, which can achieve photocatalytic reduction of carbon dioxide with high selectivity and high stability, and has higher methanol selectivity and yield.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] A method for preparing a defect-controlled ultra-thin molybdenum disulfide-loaded organic manganese complex heterostructure catalyst comprises the following steps:
[0010] Step 1, stirring and mixing molybdate and an organic sulfur-containing compound in a solvent, crystallizing and washing to obtain flaky molybdenum sulfide;
[0011] Step 2, dispersing the flaky molybdenum sulfide in a solvent and performing ultrasonic exfoliation, and obtaining defect-rich ultrathin molybdenum sulfide after centrifugation;
[0012] Step 3, mixing manganese salt, bipyridine and oxalic acid in a solvent, dispersing and washing to obtain a layered organic manganese complex;
[0013] Step 4, stirring and mixing the ultra-thin molybdenum sulfide and the layered organic manganese complex solution for reaction, and obtaining the heterogeneous structure catalyst through centrifugation, washing, drying and calcination.
[0014] After trying various transition metal elements, the present invention found that the catalyst formed by forming a heterogeneous interface with an organic manganese complex loaded with ultra-thin molybdenum sulfide rich in defects can greatly improve the adsorption and activation of CO2, resulting in the catalytic activity of H2O in the photocatalytic reaction to efficiently reduce CO2. The catalytic effect is much higher than that of the catalyst reported in the prior art, and the catalyst has suitable light absorption characteristics, can generate sufficient electron-hole pairs, improve the efficiency of separation and transfer of photogenerated electrons and holes, and effectively inhibit the rapid recombination of carriers, thereby efficiently participating in the redox process and effectively improving the yield of the target product methanol.
[0015] The molybdate includes one or a combination of two or more of sodium molybdate, potassium molybdate and ammonium molybdate;
[0016] The organic sulfur-containing compound includes one or a combination of two or more of mercaptan, thiophenol, thiourea, and disulfide;
[0017] The solvent in step 2 includes one or a combination of two or more of ethanol, isopropanol, water, N-methylpyrrolidone, and ethylene glycol.
[0018] The manganese salt includes one or a combination of two or more of manganese nitrate, manganese carbonate, manganese acetate and manganese sulfate; the bipyridine includes 2,2-bipyridine and / or 4,4-bipyridine. The manganese salt and bipyridine react easily to form an organic manganese complex.
[0019] The molar ratio of the organic sulfur-containing compound to the molybdate is 0.5-50:0.5-30, preferably 0.5-30:0.5-15, and more preferably 5-15:0.5-5. The stirring and mixing are carried out at room temperature for 2-50 hours, preferably 4-24 hours, 6-35 hours at room temperature; the crystallization temperature is 100-400°C, and the time is 6-30 hours; for example, 120°C, 160°C, 200°C, 240°C, 280°C, and the crystallization is carried out for 8 hours, 12 hours, 16 hours, 20 hours, 24 hours, 28 hours; preferably, the crystallization temperature is 140-200°C, and the crystallization time is 15-25 hours.
[0020] In step 2, the mass concentration of flaky molybdenum sulfide in the solvent is 0.01-50 mg / ml, the ultrasonic time is 1-50 h, and the ultrasonic temperature is room temperature. Preferably, the mass concentration of flaky molybdenum sulfide in the solvent is 0.1-30 mg / ml, and the time is 5-18 h. A further preferred mass concentration is 0.1-25 mg / ml, and a further preferred mass concentration is 0.1-2 mg / ml. The ultrasonic time is preferably 5-15 h, and more preferably 10-15 h.
[0021] The stripping concentration and stripping time have an important influence on the construction of defect-rich MoS2 thin-layer structures. When the solvent concentration is low, the layers are easier to separate, resulting in more defect sites; under high concentration conditions, solvent molecules may occupy a part of the potential defect sites, thereby limiting the generation of defects. On the other hand, the longer the ultrasonic time, the greater the mechanical stress and shear force on the MoS2 layer, and the more opportunities for defect formation; if the ultrasonic time is too short, the dispersion of the material will be inhibited.
[0022] In step 3, the molar ratio of manganese salt, bipyridine and oxalic acid is 0.5-50:0.5-50:0.1-80; preferably, the molar ratio of manganese salt, bipyridine and oxalic acid is 0.5-20:0.5-20:0.5-20, and further preferably, the molar ratio of manganese salt, bipyridine and oxalic acid is 0.5-8:0.5-5:0.5-5.
[0023] In step 3, the dispersion temperature is 10-60°C and the time is 1-36h. Preferably, the dispersion temperature is 20-40°C and the time is 2-6h;
[0024] Preferably, the manganese salt, bipyridine and oxalic acid can be separately dispersed in a solvent in advance, and then the three solutions are mixed and dispersed to prepare the layered organic manganese complex. Dispersing in advance helps to disperse the substances evenly and improve the reaction efficiency.
[0025] In step 4, the mass ratio of the organic manganese complex to the ultrathin molybdenum sulfide is 5-150:50-500; preferably, the mass ratio of the organic manganese complex to the ultrathin molybdenum sulfide is 5-100:50-200, and further preferably, the mass ratio of the organic manganese complex to the ultrathin molybdenum sulfide is 5-70:100-200.
[0026] In step 4, the reaction temperature is 5-60°C and the reaction time is 5-48h; preferably the temperature is 10-40°C and the reaction time is 10-24h; the solvent includes water and / or alcohols; the alcohols include methanol, ethanol, ethylene glycol, n-butanol, benzyl alcohol, etc., preferably methanol, ethanol, and ethylene glycol.
[0027] The calcination temperature is 50-450°C, and the calcination time is 2-20h; preferably, the calcination temperature is 50-400°C, more preferably 100-300°C, and more preferably 200-300°C; the calcination time is preferably 4-20h. Calcination is particularly important in the synthesis process, which is a key step in forming a heterostructure.
[0028] The product washing in each step is performed by co-washing with a specific solvent, and drying is performed at 60-80° C. for 1-6 hours, or 1-10 hours.
[0029] The present invention also provides a defect-controlled ultra-thin molybdenum disulfide loaded with an organic manganese complex heterostructure catalyst prepared by the preparation method, wherein the catalyst is composed of a layered organic manganese complex and an ultra-thin molybdenum sulfide, wherein the thickness of the ultra-thin molybdenum sulfide is 0.1-20nm, the thickness of the layered organic manganese complex is 0.5-10nm, and the total thickness of the catalyst is 0.6-30nm; the mass proportion of the Mn element in the catalyst is less than 50wt%. The manganese content is preferably 0.1-10wt%; the manganese content is further preferably 0.5-10wt%, and the manganese content is further preferably 2-8wt%.
[0030] The present invention also provides application of the heterogeneous structure catalyst in photocatalytic preparation of methanol.
[0031] The photocatalytic reaction is carried out at 10-100°C, 0.05-10MPa, and the light source is a 100-600W xenon lamp. The methanol yield is 538μmol·g cat -1 ·h -1 The methanol selectivity is above 80%. Preferably, the methanol yield is 613 μmol·g cat -1 ·h -1 The methanol selectivity is above 82%; the methanol yield is further preferably 652 μmol·g cat -1 ·h -1 Above, methanol selectivity is more than 85%;
[0032] In order to achieve high catalytic performance and stability of photocatalytic reduction of CO2 to methanol, the designed catalyst needs to have high photogenerated carrier transfer ability and utilization rate, and can improve the metastable properties of thin-layer material defects. The present invention uses defects on monolayer MoS2 as positioning sites, combines with MnBO organic ligands, forms an ultra-thin two-dimensional heterostructure, effectively inhibits the recombination of electrons and holes, and improves the structural instability of defect-rich MoS2, thereby achieving high selectivity and high stability of CO2 reduction to methanol reaction. The obtained catalyst can promote H2O to reduce CO2 under light, at low temperature and low pressure conditions, without the participation of any reaction aid or sacrificial agent, to obtain high-value chemicals such as methanol, and the selectivity and yield of methanol are greatly improved.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The present invention adopts a simple mixed loading method, using defects as positioning points to composite two ultra-thin two-dimensional semiconductors into a heterostructure, which effectively solves the activation problem of CO2 and H2O; at the same time, by regulating the amount of defects on the surface of ultra-thin MoS2, its contact with MnBO is regulated, forming a new defect energy level, which is conducive to the generation of high-energy electrons that promote the reduction reaction, thereby effectively improving the reaction activity and obtaining nearly 90% methanol selectivity, providing a practical research strategy for high-value photocatalytic CO2 conversion.
[0035] (2) The catalyst prepared by the present invention has light absorption characteristics, so it can generate sufficient electron-hole pairs under illumination conditions, improve the efficiency of separation and transfer of photogenerated carriers, and effectively inhibit the rapid recombination of electrons and holes, thereby efficiently participating in the oxidation process of H2O and the reduction process of CO2, and can promote the reduction of CO2 by H2O at low temperature and low pressure, and greatly improve the methanol selectivity and yield. The methanol yield is 652 μmol·gcat -1 ·h -1 Above, the methanol selectivity is above 85%.
[0036] (3) Compared with conventional catalysts, the preparation process of the heterostructured catalyst of organic manganese complex and molybdenum sulfide is simple, easy to operate, and the raw materials are simple and easy to obtain. It has the potential for industrial application and is suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 X-ray diffraction spectra of the heterostructure catalyst, organic manganese complex and MoS2(1) prepared in Example 1.
[0038] Figure 2 TEM image (a), EDX mapping image and EDX mapping image (b) of each element in the catalyst prepared in Example 1.
[0039] Figure 3 This is a comparison chart of the performance of heterogeneous structure catalysts prepared in Examples 1-3 for catalyzing CO2 and H2O to produce methanol.
[0040] Figure 4 This is a comparison chart of the performance of heterogeneous structure catalysts prepared in Example 1 and Example 4-5 for catalyzing CO2 and H2O to produce methanol.
[0041] Figure 5 Stability diagram of the heterogeneous structure catalyst prepared in Example 1 for catalyzing CO2 and H2O to produce methanol.
[0042] Figure 6 This is a performance diagram of the heterogeneous structure catalyst prepared in Example 1 and Comparative Example 6 catalyzing CO2 and H2O to produce methanol under the reaction condition of 6MPa. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0044] The raw materials used in the following specific embodiments were purchased from Aladdin or Sinopharm Reagent and used directly without treatment.
[0045] Example 1
[0046] Step 1, 891 mg of ammonium molybdate and 1745 mg of thiourea (the molar ratio of the two is 0.7:10.7) are placed in 30 ml of deionized water, stirred at room temperature for 3 hours, then placed in a 100 ml stainless steel autoclave, crystallized in an oven at 170° C. for 20 hours, washed with water and alcohol, and dried in a vacuum oven at 80° C. overnight to obtain petal-shaped flaky molybdenum sulfide;
[0047] Step 2, placing 200 mg of molybdenum sulfide in 500 ml of N-methylpyrrolidone (mass concentration of molybdenum sulfide is 0.4 mg / ml), ultrasonicating at room temperature for 15 h, centrifuging, and vacuum drying at 70° C. to obtain a defect-rich monolayer molybdenum sulfide, recorded as MoS2(1);
[0048] Step 3, respectively prepare three solutions, A: 822 mg of manganese nitrate hydrate is ultrasonically dispersed in 30 ml of deionized water; B: 358 mg of 2,2'-bipyridine is ultrasonically dispersed in 15 ml of methanol; C: 150 mg of oxalic acid is ultrasonically dispersed in 20 ml of deionized water, after the three solutions are evenly dispersed, the B solution and the C solution are respectively added dropwise to the A solution (the molar ratio of manganese nitrate, 2,2'-bipyridine and oxalic acid is 2.6:1.4:1.0), stirred at 30° C. for 5 hours, and then centrifuged, washed, and dried to obtain a layered organic manganese complex;
[0049] Step 4, ultrasonically disperse 48 mg of the organic manganese complex in 30 ml of deionized water, and after uniform dispersion, add 200 mg of monolayer molybdenum sulfide into the solution, stir at 30°C for 18 hours, wash, centrifuge and dry, and finally place the product in a muffle furnace. The calcination temperature is increased from 50°C to 300°C and maintained at 300°C for 15 hours to obtain a heterostructure catalyst of the organic manganese complex and molybdenum sulfide, recorded as Mn / MoS2(1).
[0050] The Mn / MoS2(1) catalyst is composed of a layered organic manganese complex and ultrathin molybdenum sulfide, wherein the thickness of the ultrathin molybdenum sulfide is 0.9 nm, the thickness of the layered organic manganese complex is 2.3 nm, and the total thickness of the catalyst is 3.5 nm; the manganese content in the heterogeneous structure catalyst prepared by calculating the input ratio of the raw materials is 5 wt%.
[0051] Figure 1 The X-ray diffraction spectra of the prepared organic manganese complex and ultrathin molybdenum sulfide heterostructure catalyst Mn / MoS2(1) and precursor MoS2(1) as well as the organic manganese complex. Figure 1 It can be seen that after the organic manganese complex is loaded on molybdenum sulfide, the crystal structure of molybdenum sulfide remains intact, but compared with unloaded molybdenum sulfide, the characteristic diffraction peak of the organic manganese complex appears in the XRD spectrum of Mn / MoS2(1).
[0052] Figure 2 a is the TEM image of the prepared 5wt% organic manganese complex and ultra-thin molybdenum sulfide heterostructure catalyst. Figure 2 a It can be seen that the organic manganese complex presents a relatively obvious thin layer structure of MnBO wrapped around MoS2, which is closely connected to the two surfaces of molybdenum sulfide, showing heterogeneous structural characteristics. This phenomenon is also confirmed in the EDX mapping of the Mn / MoS2(1) heterogeneous structure catalyst (such as Figure 2 b).
[0053] Example 2-3
[0054] According to the preparation process of Example 1, only the amount of solvent in step 2 is changed, that is, step 2 is: 200 mg of molybdenum sulfide is placed in 100 ml and 10 ml of N-methylpyrrolidone, respectively, and the corresponding molybdenum sulfide mass concentrations are 2 mg / ml and 20 mg / ml, respectively, and MoS2 with different defect contents is obtained after ultrasonic treatment for 15 hours. 200 mg of MoS2 with different defect amounts are respectively compounded with 48 mg of MnBO to obtain Mn / MoS2(3) and Mn / MoS2(6).
[0055] Embodiment 4-5
[0056] According to the preparation process of Example 1, the ultrasonic time in step 2 is changed to 5h and 10h respectively, that is, step 2 is: 200mg of molybdenum sulfide is placed in 500ml of N-methylpyrrolidone (mass concentration of molybdenum sulfide is 0.4mg / ml), ultrasonicated for 5h and 10h at room temperature respectively, after centrifugation and vacuum drying at 70°C, to obtain Mn / MoS2(1)-5h and Mn / MoS2(1)-10h with different synthesis times.
[0057] Comparative Example 1
[0058] According to the preparation process of Example 1, the calcination step in step 4 is not performed. Step 4 is: 48 mg of the organic manganese complex is ultrasonically dispersed in 30 ml of deionized water. After uniform dispersion, 200 mg of monolayer molybdenum sulfide is added to the solution, and stirred at 30°C for 18 hours. The catalyst obtained by washing, centrifugation and drying is recorded as Mn-MoS2.
[0059] Comparative Example 2
[0060] According to the preparation process of Example 1, the carrier MoS2 does not undergo the stripping step, that is, step 2 is omitted, and flaky molybdenum sulfide is directly used in step 4 to obtain Mn / MoS2.
[0061] Comparative Examples 3-5
[0062] According to the preparation process of Example 1, without changing step 1 and step 2, the type of metal nitrate in step 3 and the molar ratio thereof to bipyridine and oxalic acid are changed, that is, step 3 is: three solutions are prepared respectively, A: 745 mg of cobalt nitrate hydrate is ultrasonically dispersed in 30 ml of deionized water; B: 400 mg of 2,2'-bipyridine is ultrasonically dispersed in 15 ml of methanol; C: 150 mg of oxalic acid is ultrasonically dispersed in 20 ml of deionized water, after the three solutions are evenly dispersed, solution B and solution C are respectively added dropwise to solution A (the molar ratio of cobalt nitrate, 2,2'-bipyridine and oxalic acid is 2.1:2.1:1.0), stirred at 30°C for 5 hours, centrifuged, washed and dried to obtain a layered organic cobalt complex;
[0063] Repeat the above operation to prepare three solutions: A: 1489 mg of copper nitrate hydrate is ultrasonically dispersed in 30 ml of deionized water; B: 385 mg of 2,2'-bipyridine is ultrasonically dispersed in 15 ml of methanol; C: 170 mg of oxalic acid is ultrasonically dispersed in 20 ml of deionized water. After the three solutions are evenly dispersed, solution B and solution C are added dropwise to solution A (the molar ratio of copper nitrate, 2,2'-bipyridine and oxalic acid is 2.6:2.7:1.0), stirred at 30°C for 5 hours, and then centrifuged, washed and dried to obtain a layered organic copper complex.
[0064] Repeat the above operation to prepare three solutions: A: 909 mg of nickel nitrate hydrate ultrasonically dispersed in 30 ml of deionized water; B: 500 mg of 2,2'-bipyridine ultrasonically dispersed in 15 ml of methanol; C: 150 mg of oxalic acid ultrasonically dispersed in 20 ml of deionized water. After the three solutions are evenly dispersed, solution B and solution C are added dropwise to solution A (the molar ratio of nickel nitrate, 2,2'-bipyridine and oxalic acid is 2.4:1.81:1.0), stirred at 30°C for 5 hours, and then centrifuged, washed, and dried to obtain a layered organic nickel complex.
[0065] At the same time, the type of organic complex in step 4 is changed, that is, step 4 is: 48 mg of organic cobalt complex or organic copper complex or organic nickel complex is ultrasonically dispersed in 30 ml of deionized water, and after uniform dispersion, 200 mg of monolayer molybdenum sulfide is added to the solution, stirred at 30°C for 18 hours, washed, centrifuged and dried, and finally the obtained product is placed in a muffle furnace, the calcination temperature is increased from 50°C to 300°C, and maintained at 300°C for 15 hours to obtain heterogeneous structure catalysts of organic metal complex and molybdenum sulfide, recorded as Co / MoS2(1), Cu / MoS2(1), and Ni / MoS2(1).
[0066] Comparative Example 6
[0067] According to the preparation process of Example 1, without changing step 1 and step 2, three solutions were prepared respectively: A: 714 mg of zinc nitrate was ultrasonically dispersed in 30 ml of deionized water; B: 348 mg of 2,2'-bipyridine was ultrasonically dispersed in 15 ml of methanol; C: 120 mg of oxalic acid was ultrasonically dispersed in 20 ml of deionized water. After the three solutions were evenly dispersed, solution B and solution C were added dropwise to solution A (the molar ratio of zinc nitrate, 2,2'-bipyridine and oxalic acid was 2.4:2.2:1.0), stirred at 30°C for 3 hours, and then centrifuged, washed, and dried to obtain a layered organic zinc complex;
[0068] Step 4 is: ultrasonically disperse 48 mg of the organic zinc complex in 30 ml of deionized water, and after uniform dispersion, add 200 mg of monolayer molybdenum sulfide into the solution, stir at 30°C for 18 hours, wash, centrifuge and dry, and finally place the product in a muffle furnace. The calcination temperature is increased from 50°C to 300°C and maintained at 300°C for 15 hours to obtain a heterostructure catalyst of the organic metal complex and molybdenum sulfide, which is recorded as Zn / MoS2(1).
[0069] Catalyst performance evaluation
[0070] The photocatalytic performance of the catalysts prepared in Examples 1-5 and the catalysts prepared in Comparative Examples 1-4 was evaluated. The photocatalytic reaction was carried out in a specially made quartz closed high-pressure reaction device, and photocatalysis was achieved by simulating solar radiation with a xenon lamp.
[0071] Reaction conditions: Before the photocatalytic reaction, 40 mg of the catalyst was dispersed in the above quartz reactor, and 15 ml of deionized water was injected. Then 6 MPa of CO2 was introduced to exhaust the air in the reactor, and then the reactor was pressurized to 0.5 MPa with CO2. A 500 W xenon lamp was used for illumination, the reaction temperature was 28 ° C, and a cutoff filter (<420 nm) was used to filter out ultraviolet light in the illumination. After controlling the reaction time, the relevant products were analyzed and quantified by gas chromatography and nuclear magnetic resonance.
[0072] Table 1 Methanol yield and selectivity of catalysts of Examples and Comparative Examples
[0073]
[0074] Table 1 and Figure 3 This is a graph of methanol yields of different MoS2 and organic manganese complex heterostructure catalysts synthesized at different ultrasonic concentrations prepared in Examples 1-3. The lower the concentration, the lower the reaction activity.
[0075] Table 1 and Figure 4 The following is a comparison of the reaction performance of the heterogeneous structure catalysts of molybdenum sulfide and organic manganese complex synthesized at different ultrasonic times. By comparison, 15h is the best ultrasonic time, under which the methanol yield is the highest. On this basis, if the ultrasonic time is further extended, the reaction activity of MoS2 is still not much different from that of 15h, but its energy consumption is significantly increased.
[0076] Figure 5 It can be seen that the heterostructure catalyst of molybdenum sulfide and organic manganese complex has good stability and can maintain a high methanol yield for 50 hours.
[0077] It can be seen from Comparative Example 1 that at a calcination temperature of 300°C, the manganese organic complex is conducive to forming a relatively stable heterostructure with MoS2, effectively promoting the transfer of electrons between the two two-dimensional materials, avoiding the recombination of holes and electrons, and thus increasing the production of methanol.
[0078] It can be seen from Comparative Example 2 that the defect-rich MoS2 formed after ultrasound can be better combined with the precursor Mn complex to promote electron transfer and ultimately obtain better photocatalytic activity.
[0079] The applicant's early research found that the catalyst combined with zinc coordination and molybdenum sulfide has good photocatalytic carbon dioxide performance. Further research found that after the molybdenum sulfide is stripped, it can not only combine with the Zn organic complex to form a defect-rich heterostructure catalyst, but also reach 570μmol·gcat under near-normal pressure reaction conditions. -1 ·h -1 The methanol yield and selectivity of 85% were achieved. The defect-rich monolayer MoS2 can also be combined with organic complexes corresponding to various transition metal elements (Mn, Co, Cu, Ni) to obtain considerable CO2 photoreduction activity, among which the Mn element showed an effect far exceeding that of the zinc element. By comparing Example 1 with Comparative Examples 3-6, it can be seen that n / MoS2(1) can reach 843μmol·gcat -1 ·h -1 The methanol yield and selectivity of 94% are 1.7 times that of Zn / MoS2(1). This indicates that after Mn combines with defect-rich MoS2, due to the unsaturated electron coordination, it provides more active sites to catalyze the conversion of CO2, ultimately achieving a better catalytic activity.
[0080] In addition, in order to compare with previous studies, the photocatalytic CO2 reduction test under 6MPa reaction conditions was also carried out. Figure 6 As shown in the figure, by comparison, the combination of Mn and MoS2 does indeed more effectively promote electron transfer, inhibit the recombination of photogenerated carriers, and ultimately achieve the efficient production of methanol.
[0081] The performance of the catalyst Mn / MoS2(1) prepared in Example 1 for photocatalytic carbon dioxide reduction was compared with that of some catalysts reported in the literature in the prior art. The results are shown in Table 2. It can be seen that under photocatalytic conditions, compared with the catalysts in some literature, the Mn / MoS2(1) heterostructure catalyst has a strong ability to selectively reduce carbon dioxide through photocatalysis, and can highly selectively produce high value-added chemicals such as methanol and oxygen, which proves that the catalyst has an efficient photocatalytic effect, alleviates the problem of high-speed recombination of electron-hole pairs to a certain extent, and can effectively improve the reaction activity and stability of photocatalytic carbon dioxide reduction.
[0082] Table 2 Comparison of the performance of the catalyst of Example 1 and the catalyst of the literature for photocatalytic carbon dioxide reduction
[0083]
[0084]
Claims
1. A method for preparing a defect-controlled ultra-thin molybdenum disulfide-supported organic manganese complex heterostructure catalyst, characterized in that: Includes steps: Step 1, stirring and mixing molybdate and an organic sulfur-containing compound in a solvent, crystallizing and washing to obtain flaky molybdenum sulfide; Step 2, dispersing the flaky molybdenum sulfide in a solvent and performing ultrasonic exfoliation, and obtaining defect-rich ultrathin molybdenum sulfide after centrifugation; Step 3, mixing manganese salt, bipyridine and oxalic acid in a solvent, dispersing and washing to obtain a layered organic manganese complex; Step 4, stirring and mixing the ultra-thin molybdenum sulfide and the layered organic manganese complex solution for reaction, and obtaining the heterogeneous structure catalyst through centrifugation, washing, drying and calcination.
2. The method for preparing the defect-controlled ultra-thin molybdenum disulfide-supported organic manganese complex heterostructure catalyst according to claim 1, characterized in that: The molybdate includes one or a combination of two or more of sodium molybdate, potassium molybdate and ammonium molybdate; And / or, the organic sulfur-containing compound includes one or a combination of two or more of mercaptans, thiophenols, thioureas, and disulfides; And / or, the solvent in step 2 includes one or a combination of two or more of ethanol, isopropanol, water, N-methylpyrrolidone, and ethylene glycol.
3. The method for preparing the defect-controlled ultra-thin molybdenum disulfide-supported organic manganese complex heterostructure catalyst according to claim 1, characterized in that: The manganese salt includes one or a combination of two or more of manganese nitrate, manganese carbonate, manganese acetate and manganese sulfate; And / or, the bipyridine includes 2,2-bipyridine and / or 4,4-bipyridine.
4. The method for preparing the defect-controlled ultra-thin molybdenum disulfide-supported organic manganese complex heterostructure catalyst according to claim 1, characterized in that: The molar ratio of the organic sulfur-containing compound to the molybdate is 0.5-50:0.5-30; the stirring and mixing are carried out at room temperature for 2-50 hours; the crystallization temperature is 100-400° C., and the time is 6-30 hours.
5. The method for preparing the defect-controlled ultra-thin molybdenum disulfide-supported organic manganese complex heterostructure catalyst according to claim 1, characterized in that: In step 2, the mass concentration of flaky molybdenum sulfide in the solvent is 0.01-50 mg / ml, the ultrasonic time is 1-50 h, and the ultrasonic temperature is room temperature.
6. The method for preparing the defect-controlled ultra-thin molybdenum disulfide-supported organic manganese complex heterostructure catalyst according to claim 1, characterized in that: In step 3, the molar ratio of the manganese salt, bipyridine and oxalic acid is 0.5-50:0.5-50:0.1-80; the dispersion temperature is 10-60°C, and the dispersion time is 1-36h.
7. The method for preparing the defect-controlled ultra-thin molybdenum disulfide-supported organic manganese complex heterostructure catalyst according to claim 1, characterized in that: In step 4, the mass ratio of the organic manganese complex to the ultra-thin molybdenum sulfide is 5-150:50-500; the reaction temperature is 5-60°C, the time is 5-48h, and the solvent includes water and / or alcohols; the calcination temperature is 50-450°C, and the calcination time is 2-20h.
8. The defect-controlled ultra-thin molybdenum disulfide-supported organic manganese complex heterostructure catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The catalyst consists of a layered organic manganese complex and ultrathin molybdenum sulfide, wherein the ultrathin molybdenum sulfide has a thickness of 0.1-20 nm, the layered organic manganese complex has a thickness of 0.5-10 nm, and the total thickness of the catalyst is 0.6-30 nm; the mass proportion of the Mn element in the catalyst is less than 50 wt%.
9. Use of the heterogeneous structure catalyst according to claim 8 in photocatalytic preparation of methanol.
10. Use of the heterogeneous structure catalyst according to claim 9 in photocatalytic preparation of methanol, characterized in that: The photocatalytic reaction was carried out at 10-100℃, 0.05-10MPa, and the light source was a 100-600W xenon lamp. The methanol yield was 538μmol·g cat -1 ·h -1 Above, the methanol selectivity is above 80%.
Citation Information
Patent Citations
Molybdenum disulfide / manganese tungsten oxide nanorod composite material, preparation method thereof and application of material
CN108722442A
Transition metal doped defect-rich molybdenum disulfide as well as preparation method and application thereof
CN112844420A
Bipyridyl cobalt / graphene composite material and preparation method thereof
CN112993282A
Catalyst for preparing methanol by cyclically applying photocatalytic reduction of carbon dioxide and preparation method thereof
CN116139874A
Catalyst with heterostructure of organic zinc complex and molybdenum sulfide as well as preparation method and application of catalyst
CN116273180A